Acceptability Level of Students in Pradita Dirgantara Senior High School against E-Sport as an Extracurricular Alternative - Mikhael Bagus Pradana; Agus Kristiyanto; Siswandari Siswandari (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
E-Sportstands for Electronic Sport, E-Sport has a general meaning, namely an agility contest between individuals or groups that is not limited to physical activities only and is carried out using tools that carry out their functions electronically. During its development, E-Sport began to penetrate the world of education as a sport. Some schools have begun to introduce E-Sport through extracurricular activities, this is of course the pros and cons of students, especially male and female students. This study aims to map the level of acceptance of students at Pradita Dirgantara High School to E-Sport as an extracurricular alternative. This type of research is a descriptive study using a quantitative approach.batch 2018 and 2019. The sample in this study was taken using a random sampling technique, with a total of 75 students from two generations. Data collection used a questionnaire with the Likert scale scoring method. The data analysis used the frequency distribution formula in the form of a percentage. The results showed that the level of acceptability of students towards E-Sport as an extracurricular alternative was the highest in the group of male students of class XI followed by class XII with a percentage of 45.00% and 63.16%, while the lowest was in the group of female students of class XII and class XI with a percentage of 42.86% and 46.67%.